METHODOLOGY OF ORGANIZATION OF PEDAGOGICAL WORKING CONDITIONS BASED ON ERGONOMIC REQUIREMENTS - Djurayev Olimjon Narkulovich (American Journals, 2023)
The article describes methods of organizing pedagogical working conditions based on ergonomic requirements. Ergonomics is a science that studies human labor activity, work tools and tools, the environment and the process of their interaction.
Keywords: working conditions, ergonomics, ergonomic requirements, ergonomic approach, pedagogical work, work activity, process